블루베리 효모 발효 분말의 기능성 원료 표준화를 위한 지표성분으로서 Chlorogenic Acid 분석 및 검증 - 정수지(Su-Ji Jeong); 양희종(Hee-Jong Yang); 류명선(Myeong Seon Ryu); 서지원(Ji Won Seo); 정도연(Do-Youn Jeong) (Han'guk Sikp'um Yŏngyang Kwahakhoe chi, 2019)
블루베리 효모 발효 분말의 개별 인정형 건강기능식품 기능성 원료로 개발하기 위하여 지표성분 표준화를 위한 chlorogenic acid의 분석법 설정과 분석법에 대한 벨리데이션을 실시하였다. 벨리데이션에 앞서 chlorogenic acid의 분석을 위한 추출 용매의 농도별 수율을 조사한 결과 50% 에탄올로 추출 시 2,040.14 µg/mL로 가장 우수한 수율을 나타내어 추출 용매의 농도를 확립하였다. Chlorogenic acid의 분석은 1% acetic acid가 첨가된 water와 acetonitrile을 이동상으로 하고 Capcellpak-C18(4.6×150 mm, 5 μm) 컬럼을 사용하여 기울기 용리(gradient elution) 방법으로 분석하였다. 본 연구에서는 분석법에 대한 특이성, 직선성, 정확성과 정밀성 및 회수율을 확인하였다. Chlorogenic acid의 검량선은 상관계수(R2)가 0.9999로 우수한 직선성을 보였으며, 검출한계와 정량한계는 각각 5.38 µg/mL, 16.32 µg/mL로 나타났다. 시료 농도별 intra-day 및 inter-day 분석에서의 상대표준편차(RSD)는 각각 1.34~2.5%, 0.92~2.17%로 나왔다. 회수율 측정 결과에서는 103.03~103.36%로 나왔으며, RSD는 0.83~1.22%였다. 따라서 HPLC를 이용한 chlorogenic acid의 분석법이 블루베리 효모 발효 분말의 기능성 원료 표준화를 위한 지표성분 분석의 적합한 시험법임을 검증하였다. 또한 본 시험법에 따라 제조 공정별 블루베리 효모 발효 분말 내의 chlorogenic acid 함량을 측정하였으며, 최종 산물인 블루베리 효모 발효 분말의 chlorogenic acid 함량을 세 lot를 3회 분석하였을 때 2,032.66 µg/mL가 나왔으며, RSD 값은 0.58%로 확인되었다. 따라서 본 연구를 통해 확립한 분석법이 블루베리 효모 발효 분말의 개별인정형 건강기능식품 기능성 원료 개발을 위한 기초 자료로 활용될 것으로 사료된다. This study validated an analytical method for chlorogenic acid in blueberry yeast fermented powder (BYFP) for standardization as a functional health ingredient. Measurements of the yield according to the concentration of the extraction solvent for analyzing the level chlorogenic acid before validation showed that the extraction yield was highest at 2,040.14 µg/mL when extracted with 50% ethanol. The quantitative determination method of chlorogenic acid was optimized by HPLC analysis using a Capcellpak-C18 column with a gradient elution of 1% acetic acid in water and acetonitrile. This method was validated according to the specificity, linearity, accuracy, precision test, and recovery test. The method showed reliable linearity of the calibration curve with a R2 of 0.9999, and the limit of quantitation and the detection limit were 5.38 µg/mL and 16.32 µg/mL, respectively. The relative standard deviation (RSD) from the intra- and inter-day precision according to the chlorogenic acid concentration ranged from 1.34 to 2.5% and 0.92 to 2.17%, respectively. The recovery test ranged from 103.03% to 103.36% with RSD values from 0.83 to 1.22%. Therefore, chlorogenic acid as a marker compound in BYFP was analyzed. The amount of chlorogenic acid in BYFP was approximately 2,032.66 µg/mL after triplicate analysis, and the RSD was 0.58% using the validated method. These results suggest that the method is very useful for evaluating the marker compounds in BYFP to develop a health functional food material. KCI Citation Count: 3